EphA4 preserves postnatal and adult neural stem cells in an undifferentiated state in vivo - Khodosevich, Konstantin; Watanabe, Yasuhito; Monyer, Hannah (Journal of cell science, 2011)
In the postnatal brain, new neurons continue to be generated in two neurogenic areas, the subventricular zone of the lateral ventricles (SVZ) and the subgranular zone of the hippocampus. There is evidence that ephrins and their Eph receptors belong to a signaling network that regulates neurogenesis. On the basis of previous data, we have identified Eph receptor A4 (EphA4) as a potential regulator of neurogenesis. We showed by immunohistochemistry that in adult neurogenic niches EphA4 is expressed only by neural stem cells (NSCs). Using in vitro and in vivo assays, we demonstrated that EphA4 expression maintains NSCs in an undifferentiated state. Specifically, in neurosphere cultures Epha4 knockdown resulted in a decrease of NSC proliferation and premature differentiation. In postnatal and adult brain, Epha4 knockdown caused a decrease in NSCs in the SVZ, eventually resulting in a reduced number of postnatally generated neuroblasts. Both in vitro and in vivo effects were rescued by co-infection with a modified EphA4 that was resistant to Epha4 shRNA.
Gesehen am 01.08.2022